1997
DOI: 10.1038/sj.bmt.1700904
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic bone marrow transplantation for relapsed and refractory Hodgkin’s disease and non-Hodgkin’s lymphoma

Abstract: Summary:characteristics. and high-grade lymphomas, high-dose chemotherapy (HDC) with autologous stem cell rescue (SCR) provides adults (ages 18-60 years; median 36) underwent alloBMT for lymphoma after failure of standard chemolong-term disease-free survival in 40-60% of patients who relapse with chemotherapy-sensitive disease, and has been therapy. Twenty-one had NHL and six had HD (nodular sclerosis). Thirteen patients had primary refractory disshown to be superior to conventional salvage chemotherapy alone.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
1

Year Published

1999
1999
2003
2003

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 4 publications
1
30
0
1
Order By: Relevance
“…In our series, seven patients (46%) experienced early transplant-related deaths, while an additional patient died of bronciolitis obliterans -organizing pneumonia 32 months after transplantation. Similar transplant-related mortality has been reported by Demirer et al 28 and Dann et al 29 among patients receiving allogeneic transplants as a salvage therapy for Hodgkin's disease, non-Hodgkin's lymphoma, or acute lymphoblastic leukemia. The ultimate value of allogeneic transplantation may, therefore, depend on the ability to decrease transplant-associated mortality.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…In our series, seven patients (46%) experienced early transplant-related deaths, while an additional patient died of bronciolitis obliterans -organizing pneumonia 32 months after transplantation. Similar transplant-related mortality has been reported by Demirer et al 28 and Dann et al 29 among patients receiving allogeneic transplants as a salvage therapy for Hodgkin's disease, non-Hodgkin's lymphoma, or acute lymphoblastic leukemia. The ultimate value of allogeneic transplantation may, therefore, depend on the ability to decrease transplant-associated mortality.…”
Section: Discussionsupporting
confidence: 63%
“…Results in previously reported series of allogeneic transplantation in low-grade lymphoma are highly variable. 10,28,29 In a study including 10 patients with refractory or recurrent low-grade lymphoma, van Biesen and associates 10 reported an actuarial survival of 80% among patients receiving allogeneic transplants. Only two of 10 patients experienced transplant-related mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The engraftment and post-transplantation complications in our study were similar to those reported in the literature. 15,18,29,30 However, the five recorded deaths occurred earlier after BMT (between day 18 and day 255) and were directly due to the transplantation procedure. Two out of 10 evaluable longterm survivors relapsed 63 and 1073 days after transplantation and the remaining patient, with autologous reconstitution, had never been in CR after BMT.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22][23][24][25]27,38,44,45 Those refractory to salvage chemotherapy at the time of transplant generally have eventfree survival less than 25%, and in some cases no event-free survival 20,22 because of both increased rates of relapse and increased transplant-related mortality. This pattern is not dissimilar to that seen with autoSCT, suggesting that there is only a limited role for alloSCT to overcome chemoresistance.…”
Section: Importance Of Chemosensitivitymentioning
confidence: 99%